Adam Watkins' 4th Grade Manchester-Gate Class Tour of Fresno Bee Facility at 1921 E Street, Fresno - Watkins, Howard::::::::: (1987)
Students, teachers, and parents outside entrance Eli Setencich and Bee parking lot in background